2005
DOI: 10.1128/jb.187.6.2200-2202.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in the Decoding Center of Thermus thermophilus 16S rRNA Suggests a Novel Mechanism of Streptomycin Resistance

Abstract: A spontaneous kanamycin resistance and capreomycin resistance mutation, A1408G, in the decoding center of 16S rRNA, was identified in the extreme thermophile Thermus thermophilus. Unexpectedly, this mutation also confers resistance to streptomycin. We propose a novel mechanism of streptomycin resistance by which A1408G influences conformational changes in 16S rRNA during tRNA selection.Ribosomes from the extreme thermophile Thermus thermophilus have proven to be a rich source of structural information regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…We recently reported the finding of streptomycin resistance conferred by the A1408G mutation and proposed one possible mechanism (22). In the present study, we also observed that the C1409G mutation confers comparable levels of streptomycin resistance (Table 4), presumably by conformational distortion due to the resulting G-G mismatch.…”
Section: Resultssupporting
confidence: 72%
“…We recently reported the finding of streptomycin resistance conferred by the A1408G mutation and proposed one possible mechanism (22). In the present study, we also observed that the C1409G mutation confers comparable levels of streptomycin resistance (Table 4), presumably by conformational distortion due to the resulting G-G mismatch.…”
Section: Resultssupporting
confidence: 72%
“…CmnU is a homolog of 16S rRNA methyltransferases that are known to confer resistance to kanamycin and apramycin by modifying residue A1408 (E. coli numbering) of the 16S rRNA (16). The relevance of this finding is that mutations in the analogous residue in M. tuberculosis and M. smegmatis 16S rRNA result in VIO and kanamycin resistance (32) and a mutation in the analogous residue of Thermus thermophilus results in CMN resistance (13). Furthermore, the enzyme TlyA from M. tuberculosis that methylates both 16S and 23S rRNA to make the ribosome more sensitive to CMN methylates residue C1409 of the 16S rRNA (18).…”
Section: Resultsmentioning
confidence: 91%
“…What is not clear is if changes in the dynamics of A1492 and A1493 actually contribute to the resistance phenotype. We previously found that the A1408G base substitution confers streptomycin resistance in T. thermophilus (36). A1408 is located on the far side of helix 44 away from the central pseudoknot and the contacts with streptomycin, suggesting that changes in conformational dynamics could extend some distance.…”
Section: Resultsmentioning
confidence: 99%
“…We previously described the isolation and characterization of spontaneous Str r mutants of the thermophilic bacterium T. thermophilus with amino acid substitutions in ribosomal protein S12 (35) or base substitutions in 16S rRNA (24,36). Mutant ribosomes with base substitutions in the central pseudoknot exhibit altered reactivity to base-specific chemical probes, suggesting an effect of the mutations on the hydrogen-bonding arrangement of the pseudoknot (24).…”
mentioning
confidence: 99%